Microsoft Power Platform Solution Architect's Handbook an Expert's Guide to Becoming a Power Platform Solution Architect and Preparing for the PL-600 Exam - Herrera, Hugo (Packt Publishing, Limited, 2022)
Gain expertise in solution architecture and master all aspects of Power Platform, from data and automation to analytics and security Key Features Become a full-fledged Power Platform expert and lead your solutions with conviction and clarity Adopt a consistent, systematic, and advanced approach to solution architecture Work on practical examples and exercises to develop expert-level skills and prepare for certification Book Description If you've been looking for a way to unlock the potential of Microsoft Power Platform and take your career as a solution architect to the next level, then look no further--this practical guide covers it all. Microsoft Power Platform Solution Architect's Handbook will equip you with everything you need to build flexible and cost-effective end-to-end solutions. Its comprehensive coverage ranges from best practices surrounding fit-gap analysis, leading design processes, and navigating existing systems to application lifecycle management with Microsoft Azure DevOps, security compliance monitoring, and third-party API integration. The book takes a hands-on approach by guiding you through a fictional case study throughout the book, allowing you to apply what you learn as you learn it. At the end of the handbook, you'll discover a set of mock tests for you to embed your progress and prepare for PL-600 Microsoft certification. Whether you want to learn how to work with Power Platform or want to take your skills from the intermediate to advanced level, this book will help you achieve that and ensure that you're able to add value to your organization as an expert solution architect. What you will learn Cement the foundations of your applications using best practices Use proven design, build, and go-live strategies to ensure success Lead requirements gathering and analysis with confidence Secure even the most complex solutions and integrations Ensure compliance between the Microsoft ecosystem and your business Build resilient test and deployment strategies to optimize solutions Who this book is for This book is for solution architects, enterprise architects, technical consultants, and business and system analysts who implement, optimize, and architect Power Platform and Dataverse solutions. It will also help anyone who needs a detailed playbook for architecting and delivering successful digital transformation projects that leverage Power Platform apps and the Microsoft business apps ecosystem. A solid understanding of Power Platform configuration and administration, Power Automate processes, Power Apps Portals, Canvas Apps, Dataverse Plugins, and Workflow Capabilities is expected.